STUDIES ON PRODUCTION OF LACCASE ENZYME BY WHITE ROT FUNGI - Ozan, Vildan Aykut; Ataci, Nese; Arisan, Inci (YILDIZ TECHNICAL UNIV, 2014)
In this study was investigated laccase activity from six white rot fungi collected from Yildiz Technical University Davutpasa Campus. Laccase enzyme is known to have produced as secondary metabolites by white rot fungi. The samples were taken from four different regions of fungi, the inner, outer, top hats and hats, including. The best storage conditions for fungi were detected. Fungi were cultivated in two different solid agar agar medium and are detected in which are fungi growth conditions the most active and without contamination. Then, pure cultures of fungi were inoculated into the two different containing trace elements and trace elements free laccase-production medium. Comparison by two different media the highest laccase activity were determined. In trace element-free medium with 5g/L-1 glucose, laccase activity was found to be 0.06 UmL(-1). However, the highest laccase activity in medium containing trace elements and 10 gL(-1) glucose were determined as 0.25 UmL(-1).
Keywords: White rot fungi; laccase activity; Engineering